ELECTRICAL AND MECHANICAL CHARACTERISTICS OF A VERY FAST LOBSTER MUSCLE - Mendelson, Martin (The Rockefeller University Press, 1969)
The remotor muscle of the second antenna of the American lobster is functionally divided into two parts. One part produces slow, powerful contractions and is used for postural control. The other part produces very brief twitches, can follow frequencies over 100/sec without fusion and is probably used for sound production. This great speed is due, in part, to synchronous arrival of nerve impulses at multiple terminals, a very brief membrane electrical response and electrical continuity throughout large volumes of sarcoplasm. Calculations indicate that the very extensive sarcoplasmic reticulum is probably responsible for the rapid decline of tension in this muscle.